TESTING THE EFFECTIVENESS OF ORGANIC ACIDS AS A PRESERVATIVE OF ANIMAL FEED INGREDIENTS - Rizqa Adisti; Wijayanti Indah; Retanani Yuli (Fakultas Pertanian Universitas Majalengka, 2021)
This research was conducted in the Laboratory of Feed Industry Technology, Faculty of Animal Husbandry, Bogor Agricultural University, Bogor. The purpose of this study was to determine the effectiveness of using organic acids as preservatives in feed ingredients in the form of pollard and wheat bran based on physical parameters. This study used a completely randomized design with 2 factorials in the form of feed type and organic acid type with 3 replications, samples were stored for 6 weeks and then data were collected in the form of moisture content, pile angle, pile density and specific gravity. The results showed that organic acids affected the moisture content but had no effect on pile density, pile angle and specific gravity. The type of feed affects the value of moisture content, pile angle, pile density and specific gravity. Based on the results of the effectiveness index test, it is known that the total yield value on pollard with 1% lauric acid is 0.64, sorbic acid is 0.35 and propionic acid is 0.77, while wheat bran with lauric acid is 1.07 at -1 sorbic acid. .39 and in propionic acid 2.64. The conclusion of this research is that propionic acid can be used as a preservative for pollard and wheat bran